Implementation of Ergonomics to Improve Health Quality - Sartono, Sartono; Rohimah, Anni; Fitriyanto, Abdul Rouf; Firdaus, Mallika Salwa (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This research discusses the implementation of ergonomics in everyday life, both in the fields of education, manufacturing, and services. Various health complaints can be addressed through ergonomics. Ergonomics-related solutions include product, facility, and work position design, as well as health activities. The purpose of this study was to investigate the implementation of ergonomics in improving health. Methodology: This research uses a literature review with the PRISMA framework. The tools used in this research are Publish or Perish 8, Zotero, and Vosviewer. Of the 54 articles, 15 met the requirements for further analysis. Results: 4 articles proposed ergonomic improvements to reduce musculoskeletal disorders (MSDs), including stretching. There are 3 articles proposing to improve health quality by integrating with the Occupational Health and Safety System, including the use of Personal Protective Equipment (PPE). Applications/Originality/Value: A total of 3 articles proposed improving health in education, including the use of ergonomic bags and ergonomic facility improvements.